INFORMATION TECHNOLOGY DESIGNATED TO MONITOR TRANSPORT AND VEHICLES IN ROAD TRANSPORT - Halaj, Dusan (Doprava a spoje, 2012)
This paper is focused on information technology for monitoring of transport and vehicles. The paper describes individual functions of information technologies - Infocar and Commander. These functions can be used by carriers not only for cost optimization, but also for ensuring of transport safety as well.